2014
DOI: 10.1097/qai.0b013e3182a14f7e
|View full text |Cite
|
Sign up to set email alerts
|

Retention Among ART Patients in the Highlands of Papua New Guinea

Abstract: The PAPUA model seems to be a promising intervention although it is inextricably linked to the limitations posed by a resource-constrained health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This study observed significantly lower attrition rates for patients two years after ART initiation in decentralized versus centralized services (9.9 per 100 person-years at decentralized vs. 20.8 per 100 person years at centralized). Similar results were found in a study in Papua New Guinea [ 43 ]. The PAPUA model decentralized care from regional hospitals to rural health district facilities and coordinated patient and provider support.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This study observed significantly lower attrition rates for patients two years after ART initiation in decentralized versus centralized services (9.9 per 100 person-years at decentralized vs. 20.8 per 100 person years at centralized). Similar results were found in a study in Papua New Guinea [ 43 ]. The PAPUA model decentralized care from regional hospitals to rural health district facilities and coordinated patient and provider support.…”
Section: Resultssupporting
confidence: 92%
“…We identified four retrospective observational cohort studies that examined decentralization of health services; two were good quality and two were fair quality. Two of these studies were conducted with adult PLHIV only [ 43 , 44 ] and two included adolescents and adults, but did not report results separately for adolescents [ 45 , 46 ]. The decentralization interventions typically consisted of shifting service delivery for all patients from a higher-tier health facility (such as a regional hospital) to a lower-tier health facility (such as a primary health clinic).…”
Section: Resultsmentioning
confidence: 99%
“…This PPTCT program was part of a provincial network of centrally-coordinated decentralized HIV service delivery centers (32). Antenatal testing for HIV, syphilis, and hemoglobin was provided by linked clinics serving the populace of Eastern Highlands in 20 locations, 10 of which also provided adult ART.…”
Section: Methodsmentioning
confidence: 99%
“…Now termed the Patient and Provider Unified Approach (PAPUA), the model seeks to address important patient barriers to health, including difficult access to health care, HIV-related stigma, and extreme poverty, while also emphasizing the need for stronger provider support through training, mentorship, and supervision (32). PAPUA includes a comprehensive, case management–led PMTCT program, which provides support in diagnosis disclosure to partners and outreach to partners and children for testing and support.…”
mentioning
confidence: 99%
“…At the time of my research in 2011, 3 its ARV treatment program operations had been funded through a public sector-NGO partnership for six years (Das et al, 2014). Clinic A served patients with HIV/AIDS on Mondays and Wednesdays and patients with other STIs on Tuesdays and Thursdays.…”
Section: A History Of the Papua New Guinean Clinicmentioning
confidence: 99%